Optimization of Multiple Response Using Taguchi-WPCA In ST 60 Tool Steel Turning Process With Minimum Quantity Cooling Lubrication (MQCL) Method - Dian Ridlo Pamuji; Muhammad Abdul Wahid; Abdul Rohman; Achmad As’ad Sonief; Moch Agus Choiron (Graduate Program of Syiah Kuala University, 2018)
A research was conducted for the optimization of the turning process st 60 tool steel with multiple performance characteristics based on the orthogonal array with Taguchi-WPCA method. Minimum Quantity Cooling Lubrication (MQCL) metode was applied as a coolant. The experimental studies were conducted under varying the cutting speed, feeding, depth of cut and type of coolant. The optimized multiple performance characteristics were surface roughness, and material removal rate. An orthogonal array, signal-to-noise ratio, grey relational analysis, weighted pricipal component analysis and analysis of variance were employed to study the multiple performance characteristics. Experimental results show that cutting speed gives the highest contribution for minimize of surface roughness and maximize of material removal rate, followed by feeding speed, type of coolant and depth of cut. The minimum of surface roughness and maximize of material removal rat could be obtained by using the values of cutting speed, feeding speed, depth of cut and type of coolant of 172.95 m/minute, 0.053 mm/rev, 0.25 mm, and vegetable oil as a coolant respectively.